GAMBARAN FUNGSI GINJAL PASIEN DIABETES MELITUS TIPE II DI PUSKESMAS TLOGOSARI KULON KOTA SEMARANG - Rukminingsih, Fef; Julianti, Carla (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Type II Diabetes Mellitus (DMTII) patients who are not treated properly can experience decreased renal function. The use of oral hypoglycemic drugs (OHG) can cause a decrease in renal function. Glomerular Filtration Rate (GFR) can describe a decrease in renal function. The aim of this study was to determine the description of renal function in DMTII patients at the Tlogosari Kulon Health Center, Semarang City. This research is a descriptive observational study. The sampling technique used was purposive sampling. Data was obtained from medical records of DMTII patients for the period September–December 2022. The inclusion criteria were patients with DMTII who received OHG therapy for at least one year, aged ≥45 years, had the most recent serum creatinine examination, with or without comorbidities. If the patient's data is incomplete or the patient has a history of renal problems, they will be excluded. Based on the research results, it was discovered that there were 55 DMTII patients, consisting of 39 patients (70.90%) women and 16 patients (29.10%) men. A total of 29 patients were aged between 60-69 years (52.73%). A total of 39 patients had comorbidities such as hypertension and/or dyslipidemia. A total of 76.36% received OHG combination therapy. Forty percent of patients experienced a decrease in GFR from mild-moderate to severe. The decrease in GFR is caused by the amount of OHG consumed and comorbid hypertension